Cardiac surgery and Brugada syndrome: operative considerations. (27th July 2021) - Singh, Sandeep; Chokkarapu, Seshu P; O'Nunian, Sean; Modi, Amit
Abstract: Brugada syndrome is an uncommon arrhythmic disease due to abnormality in myocardial transmembrane sodium channels and is associated with sudden death due to ventricular arrhythmias. We report our strategy and highlight precautions to reduce the risk of perioperative arrhythmias in a patient with Brugada pattern who underwent successful coronary artery bypass grafting. Abstract : Brugada syndrome (BrS) affects 5 in 10 000 people with preponderance to the male gender and Asian ethnicity [1].